Mathematical foundations of the theory of dimensions and similarity - J., Rychlewski (Vietnam Journal of Mechanics, 1980)
In this work, we present a stringent axiomatic model of computation using dimensional quantities. This model is the dimensional scalar space. We use the axiomatic method to introduce the concept of dimensional scalar space. Then, the dimensional quantities will be not the aggregates of numbers with respect to a system of units assumed ad hoe, but elements of a set defined a priori.